Simple Flow-Based System with an In-Line Membrane Gas–Liquid Separation Unit and a Contactless Conductivity Detector for the Direct Determination of Sulfite in Clear and Turbid Food Samples - Aulia Ayuning Tyas; Thitaporn Sonsa-ard; Kanchana Uraisin; Duangjai Nacapricha; Phoonthawee Saetear (Membranes, 2020)
This study presents a simple flow-based system for the determination of the preservative agent sulfite in food and beverages. The standard method of conversion of sulfite ions into SO2 gas by acidification is employed to separate the sulfite from sample matrices. The sample is aspirated into a donor stream of sulfuric acid. A membrane gas–liquid separation unit, also called a ‘gas-diffusion (GD)’ unit, incorporating a polytetrafluoroethylene (PTFE) hydrophobic membrane allows the generated gas to diffuse into a stream of deionized water in the acceptor line. The dissolution of the SO2 gas leads to a change in the conductivity of water which is monitored by an in-line capacitively coupled contactless conductivity detector (C4D). The conductivity change is proportional to the concentration of sulfite in the sample. In this work, both clear (wine) and turbid (fruit juice and extracts of dried fruit) were selected to demonstrate the versatility of the developed method. The method can tolerate turbidity up to 60 Nephelometric Turbidity Units (NTUs). The linear range is 5–25 mg L−1 SO32− with precision <2% RSD. The flow system employs a peristaltic pump for propelling all liquid lines. Quantitative results of sulfite were statistically comparable to those obtained from iodimetric titration for the wine samples.